Gamification in Early Childhood Education: A Novel Adaptive Learning Framework for Enhancing Cognitive and Social Skills in Kindergarten Students - Wijoyo, Agung (Journal of Games, Game Art, and Gamification, 2025)
Gamification has emerged as a transformative pedagogical strategy in early childhood education, fostering cognitive and social skill development through interactive and reward-based learning mechanisms. This study investigates the impact of gamification on kindergarten students' cognitive and social skills using a mixed-method experimental design involving 150 children (ages 4–6). Participants were divided into an experimental group (n=75) exposed to a gamified learning environment and a control group (n=75) following traditional instructional methods. The study employed pre-test and post-test assessments alongside Structural Equation Modeling-Partial Least Squares (SEM-PLS) for quantitative analysis, while qualitative insights were obtained through classroom observations and teacher interviews. Findings reveal that problem-solving skills significantly influence attention (β = 1.00, p < 0.001), whereas memory skills have no statistically significant effect (β ≈ 0, p = 0.50) . Post-test results indicated that students in the gamified group showed substantial improvements in problem-solving (Pre: 60.1 → Post: 82.3, p < 0.001) and attention span (Pre: 55.4 → Post: 79.8, p < 0.001) compared to the control group**. Additionally, 88% of teachers reported enhanced student motivation, and 95% of children found gamified learning more engaging than conventional approaches. These results underscore gamification's efficacy in enhancing problem-solving skills, attention, and motivation among young learners. The findings highlight the importance of integrating adaptive gamification frameworks into early education curricula to optimize learning experiences. This study contributes to the growing body of research on digital pedagogical strategies and offers valuable insights for educators and policymakers seeking to implement evidence-based gamification interventions in early childhood education.